Nilna Fauza Ushul Fikih Sebagai Epistemologi Dan Model Penelitian Hukum Islam - Nilna Fauza (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2018)
The study of Islamic law is the oldest branch of Islamic sciences and has been developed since the tabi'in era and continues to the present day. It's just that in these Islamic studies, Islamic law research seems to be more focused on atomistic and textual approaches. Speaking of Islamic law certainly cannot be separated from ushul fiqh (Islamic legal theory) because this knowledge has become the basic framework in establishing Islamic law so far. The methodology of ushul fiqh is considered as one of the models for solving the problems of Muslims found by the world of Islamic thought and not shared by other people. Jurisprudence is still considered and assumed and is believed to be one of the means to solve the problems of the contemporary people or even future problems. Jurisprudence has functions and roles similar to logic in philosophy. If logic can prevent someone from making a mistake in arguing, then ushul fiqh prevents a faqih from making a mistake in deviating the law, then it is clear that ushul fiqh can also be called the epistemology of Islamic law. The use of ushul fiqh still needs to be maximized so that ushul fiqh as a method of legal discovery which is part of Islamic law research truly functions properly. In general, Islamic law research is divided into two parts: (1) research on descriptive Islamic law (wasfi), and (2) research on normative / prescriptive Islamic law (mi'yari).